2015
DOI: 10.1007/s10903-014-0155-z
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Migrant Effect on Smoking Behavior Among Asian Immigrants in the United States

Abstract: Healthy migrant effect (HME) of immigrants has been evidenced in various heath aspects. However, few studies have explored the applicability of HME on Asian immigrants' health risk behavior-smoking. This study used three waves of Current Population Survey-Tobacco Use Supplement data, 1998-1999, 2005-2006, and 2010-2011, to compare the rates of being a current smoker among Asian immigrants and United States born citizens. Further, the odds ratios of gender, age, marital status, socioeconomic status, years of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 16 publications
6
15
0
Order By: Relevance
“…Second, contrary to earlier study that show a decline in smoking rates after long‐term residence among some immigrants groups, we found a clear indication of convergence of smoking behaviour of immigrants from NESC with NB respondents after 20 or more years of residence in Australia. However, our results are similar to other studies on Asian immigrants in Australia and other immigrant receiving countries . This observed increase in smoking prevalence of immigrants from NESC with increased DoR in the host country could be explained by processes of acculturation .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Second, contrary to earlier study that show a decline in smoking rates after long‐term residence among some immigrants groups, we found a clear indication of convergence of smoking behaviour of immigrants from NESC with NB respondents after 20 or more years of residence in Australia. However, our results are similar to other studies on Asian immigrants in Australia and other immigrant receiving countries . This observed increase in smoking prevalence of immigrants from NESC with increased DoR in the host country could be explained by processes of acculturation .…”
Section: Discussionsupporting
confidence: 91%
“…First, with respect to the lower prevalence of smoking among immigrants from NESC found in this study, our patterns are consistent with most of the earlier studies comparing immigrants from non‐English speaking backgrounds to the host population in Australia and North America . But, in contrast to the earlier studies showing higher smoking prevalence among British‐born and North American immigrants compared with NB Australians, this study found no differences in smoking between immigrants from ESC and NB Australians.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Prior studies have found that most immigrant subgroups, including black immigrants, are less likely to smoke than their native-born racial/ethnic counterparts upon arrival in the United States ( Acevedo-Garcia et al, 2005 , King et al, 1999 , Siahpush et al, 2009 , Singh and Siahpush, 2002 ). Smoking rates among immigrants, however, tend to increase as their tenure of U.S. residence increases ( Acevedo-Garcia et al, 2010a ; Alcántara et al, 2015 ; Kuerban, 2016 ; Leung, Ang, Thumboo, Wang, Yuan & Koh, 2014 ; Pérez-Stable et al, 2001 ; Singh & Siahpush 2002 ), a factor often thought to produce a convergence in health outcomes between immigrants and the U.S.-born. While a number of studies have investigated changes in smoking behavior among first-generation immigrants, several gaps exist in the extant literature on smoking, particularly among blacks in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has suggested that selective migration (e.g., individuals with the best health profiles in the origin country are more likely to move to the United States) and immigrant cultural practices that promote good health behaviors play a significant role in producing immigrants’ initial health advantage ( Jasso, Massey, Rosenzweig & Smith, 2005 ). Researchers have argued that changes in health behaviors, particularly smoking patterns, are one of the primary factors that generate the decline in immigrants’ health as their tenure of U.S. residence increases ( Gorman et al, 2014 , Kuerban, 2016 , Siahpush et al, 2009 ). Singh and Siahpush (2002) showed that while newly arrived immigrants were 52 percent less likely to smoke compared to their U.S.-born counterparts, these nativity advantages decreased to 32 and 18 percent, respectively, for those residing in the United States for 10–15 and more than 15 years.…”
Section: Introductionmentioning
confidence: 99%